Sex differences in metabolism and cardiometabolic disorders. Issue 5 (October 2018) - Chella Krishnan, Karthickeyan; Mehrabian, Margarete; Lusis, Aldons J.
Abstract : Purpose of review: Sex differences are pervasive in metabolic and cardiovascular traits, yet they have often been ignored in human and animal model research. Sex differences can arise from reversible hormonal effects, from irreversible organizational (developmental) processes, and from gene expression differences from the X and Y chromosomes. We briefly review our current understanding of the impact of these factors in metabolic traits and disorders, with an emphasis on the recent literature. Recent findings: Novel sex differences continue to be identified for metabolic and cardiovascular traits. For example, it is now clear that gut microbiota tend to differ between men and women, with potentially large implications for disease susceptibility. Also, tissue-specific gene regulation differs between men and women, contributing to differential metabolism. These new insights will open up personalized therapeutic avenues for cardiometabolic diseases. Summary: Sex differences in body fat distribution, glucose homeostasis, insulin signaling, ectopic fat accumulation, and lipid metabolism during normal growth and in response to hormonal or nutritional imbalance are mediated partly through sex hormones and the sex chromosome complement. Most of these differences are mediated in a tissue-specific manner. Important future goals are to better understand the interactions between genetic variation and sex differences, and to bring an understanding of sex differences into clinical practice.